ANALISIS YURIDIS PERTIMBANGAN HAKIM TERHADAP KORBAN EKSPLOITASI SEKSUAL DALAM TINDAK PIDANA PERDAGANGAN ORANG - Nadya Alifia Hafsah; Syahrul Ibad; Ahmad Yunus (Fakultas Ilmu Sosial dan Humaniora, 2026)
A judge’s decision is the final result of a long process in criminal law, and within that decision, there is the fate of an individual who is found guilty of committing a criminal act. The format of a judge’s decision has been regulated in Article 197 of the Criminal Procedure Code (KUHAP), which consists of both material and formal requirements. This research is also conducted to understand the regulation of sexual exploitation as stated in Law No. 21 of 2007 concerning the Eradication of Human Trafficking Crimes. In this case, the author is particularly interested in examining the indictment submitted by the public prosecutor (JPU) for the defendant. The purpose of this research is also to evaluate the accuracy of the public prosecutor in formulating/deciding their indictment This research uses a normative juridical method and an approach based on the law, with data collected through library research and analyzed using a perspective technique. The discussion results show that the actions carried out by the defendant have fulfilled the elements in Article 2 paragraph (1) of Law No. 21 of 2007 concerning the Eradication of Human Trafficking Crimes. Therefore, the judge’s decision was not entirely accurate, as the public prosecutor was not thorough or careful enough in drafting the indictment. As a result, the penalty imposed by the panel of judges did not align with the defendant’s actions.